Raising the sugar content--orchid bees overcome the constraints of suction feeding through manipulation of nectar and pollen provisions. - Tamara Pokorny; Klaus Lunau; Thomas Eltz (PLoS ONE, 2014)
Unlike most other bees, the long-tongued orchid bees ingest nectar using suction feeding. Although long tongues allow exploitation of flowers with deep spurs, the energy intake rate is optimal at 10-20% lower nectar sugar concentrations compared to that of lapping bees. This constraint might be compensated by a higher digestive throughput. Additionally, orchid bees might evaporate water from regurgitated droplets of crop contents. We found male Euglossa championi (n = 10) and Euglossa dodsoni (n = 12) to regularly regurgitate droplets of crop content to the base of their proboscis, generating a fluid film between the proximal parts of the galeae, glossa and labial palps. Rhythmic movements of the proboscis may help to increase convection. There was a significant change in sugar concentration between the initially imbibed solution and the resulting crop content (P<0.05) and the time individual bees had engaged in this liquid exposure behavior was positively correlated with the resulting crop sugar concentration. Female Euglossa townsendi and Euglossa viridissima showed the same behavior. Additionally, they manipulated their nectar-enriched pollen provisions for extensive periods of time before deposition in brood cells. The deposited pollen loads (n = 14) showed a significantly higher sugar concentration than the sugar-water available to the bees (P<0.001). Thus, both male and female euglossines show behaviors that promote evaporative water loss from nectar. We suggest that the behaviors have evolved in concert with suction feeding on dilute nectar from deep floral tubes.